Electrophysiological characterization of a diverse group of sugar transporters from Trichoderma reesei - Sami Havukainen (Nature Portfolio, 2021)
Abstract Trichoderma reesei is an ascomycete fungus known for its capability to secrete high amounts of extracellular cellulose- and hemicellulose-degrading enzymes. These enzymes are utilized in the production of second-generation biofuels and T. reesei is a well-established host for their production. Although this species has gained considerable interest in the scientific literature, the sugar transportome of T. reesei remains poorly characterized. Better understanding of the proteins involved in the transport of different sugars could be utilized for engineering better enzyme production strains. In this study we aimed to shed light on this matter by characterizing multiple T. reesei transporters capable of transporting various types of sugars. We used phylogenetics to select transporters for expression in Xenopus laevis oocytes to screen for transport activities. Of the 18 tested transporters, 8 were found to be functional in oocytes. 10 transporters in total were investigated in oocytes and in yeast, and for 3 of them no transport function had been described in literature. This comprehensive analysis provides a large body of new knowledge about T. reesei sugar transporters, and further establishes X. laevis oocytes as a valuable tool for studying fungal sugar transporters.